Satisfaction of the Creative Class with Living in Szczecin: a Relationship Perspective - Bąkowska, Sylwia (Quaestiones Geographicae, 2012)
This paper presents a set of criteria for measuring the satisfaction of the creative class derived from living in Szczecin. For this purpose, data from a telephone survey sample of the Szczecin creative class was collected*. On the basis of these criteria, the satisfaction level is estimated in the light of such factors as the attractiveness of and access to urban amenities, the city’s aesthetic values, and the attitude towards the closest neighbourhood. As a result, the satisfaction level reflects the relationship between the creative class and the local government. Also, this level decides the choice of representatives of the creative class as to whether to continue living in Szczecin or move out.